Inovasi Dan Diseminasi Ilmu Pengetahuan Teknologi Dalam Mendukung Tanjung Jabung Barat, Provinsi Jambi Menuju Kawasan Mandiri Palma - Setyawan, Hendrix Yulis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2022)
Teluk Kulbi Village is one of the villages in Betara District, Tanjung Jabung Barat Regency, Jambi Province, which has potential in the plantation sector, especially areca nut. The Mandiri Palma area is defined as an area development where the community can be independent from various aspects such as food, economy, energy based on palm commodities. However, so far, the people of Teluk Kulbi Village have problems and the lack of innovation in derivative products. The solutions offered to overcome these problems are diversifying food and non-food palm-based, especially areca nut and coconut, processing palm waste, developing palm waste-based creative industries, and pioneering Mandiri Palma areas. Community empowerment around Teluk Kulbi Village has resulted in several diversification of areca-derived products such as “Papident” herbal toothpaste, “Kopinang” drink, areca gum, palm syrup, briquettes from betel nut waste, souvenirs from betel nut, and a master plan for an independent palm area.